Pengaruh Knowledge Sharing Intention terhadap Innovative Performance di Kalangan Pegawai Profesional - Gusti, Triningtyas Elisabeth Putri; Putrawangsa, Dian; Caroline, Angela; Kornarius, Yoke Pribadi; Gunawan, Agus (Jurnal Manajemen dan Organisasi, 2025)
The digital era positions knowledge as a primary asset for fostering innovation and competitive advantage. Information and communication technology (ICT), particularly artificial intelligence (AI), plays a critical role in enhancing efficiency and creating new opportunities. A company’s innovative performance is strongly influenced by employees’ innovative work behavior, including idea generation, experimentation, and risk-taking. Knowledge sharing among employees is also essential in supporting organizational innovation. This study aims to examine the mediating role of innovative work behavior (IWB) in the relationship between knowledge sharing intention (KSI) and innovative performance (IP) among knowledge-based workers in Indonesia. The research employed Partial Least Squares Structural Equation Modeling (PLS-SEM), consisting of measurement model evaluation and structural model assessment. The results indicate significant relationships (p < 0.001) between KSI and IWB (O = 0.625), IWB and IP (O = 0.344), and KSI and IP (O = 0.343). These findings confirm that IWB mediates the relationship between KSI and IP, highlighting the crucial role of innovative work behavior in optimizing the impact of knowledge sharing on innovative performance.